Using The Picture and Picture Learning Strategy in Learning Writing Skill at Islamic State Junior High School 5 of Bojonegoro - Sri Wahyuni; Dewi Chamidah; Bisri Mustofa (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Picture and Picture is one of the learning strategies that use picture media in education. This strategy is active, creative and fun. Writing skills is one of the important in Learning Arabic. However the students of seventh class Islamic state Junior High School 5 Bojonegoro have many difficulties in writing sentences or simple paragraphs, because they feel bored and learning strategies used low attractive.The input in this research is quantitative and the research method used is the experimental method. The objectives of the research are to find out the use of picture and picture learning strategy in teaching writing skill in MTsN 5 Bojonegoro and to calculate the measurement of effectiveness of using picture and picture learning strategy in developing writing skill in MTsN 5 Bojonegoro. The input in this research is quantitative and the research method used is the experimental method. The results of this research are that the use of the picture and picture strategy is “effective”, considering the result of the castration t: 11.75 greater than the degree of t-tables at the 1% level (2,000), and greater than the degree of t-tables at the 5% level (2,660). ) . By that, (Ha) are acceptable, and (H0) is rejected, meaning that the use of the Picture and Picture strategy is